2008
DOI: 10.1016/j.pbb.2008.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping, but not identical, discriminative stimulus effects of the neuroactive steroid pregnanolone and ethanol

Abstract: Many behavioral effects of neuroactive steroids are mediated by GABA(A) receptors; however, other receptors might be involved. Ethanol has a complex mechanism of action, and many of the same receptors have been implicated in the effects of neuroactive steroids and ethanol. The goal of this study was to determine whether actions of neuroactive steroids and ethanol at multiple receptors result in similar discriminative stimulus effects. Rats discriminated 5.6 mg/kg of pregnanolone while responding under a fixed-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…During this period of testing, rate-decreasing effects were evident following administration of the training dose in each rat discriminating 7.5 mg/kg from vehicle. This apparent increased sensitivity to pregnanolone has been observed previously when large training doses of pregnanolone were used (rate-decreasing effects: Gerak et al 2008; seizures: Shannon et al 2005). When these rate-decreasing effects were observed, the training dose was temporarily decreased to 5.6 mg/kg and the frequency of vehicle training sessions was increased.…”
Section: Methodssupporting
confidence: 77%
“…During this period of testing, rate-decreasing effects were evident following administration of the training dose in each rat discriminating 7.5 mg/kg from vehicle. This apparent increased sensitivity to pregnanolone has been observed previously when large training doses of pregnanolone were used (rate-decreasing effects: Gerak et al 2008; seizures: Shannon et al 2005). When these rate-decreasing effects were observed, the training dose was temporarily decreased to 5.6 mg/kg and the frequency of vehicle training sessions was increased.…”
Section: Methodssupporting
confidence: 77%
“…Given the opposing ways in which pregnanolone and DHEA interact with the GABA A receptor complex, however, pregnanolone would likely serve more as a “substitution” therapy than DHEA. Consistent with this notion are data from this laboratory and others demonstrating that pregnanolone and other 3α-hydroxy neurosteroids have largely overlapping discriminative stimulus effects with ethanol (Bowen, Purdy, & Grant, 1999; Gerak, Moerschbaecher, & Winsauer, 2008; Ginsburg & Lamb, 2005), whereas DHEA and its sulfated form do not (Bienkowski & Kostowski, 1997; Gurkovskaya & Winsauer, 2009). There are also published data indicating that pregnanolone has reinforcing and discriminative stimulus effects in monkeys similar to the barbiturates, another class of drugs that positively modulate the GABA A receptor complex (Rowlett et al, 1999).…”
Section: Discussionsupporting
confidence: 62%
“…However, additional receptor subtypes not tested include sigma receptors and metabotropic glutamate receptors (Besheer et al , 2006). For example, previous studies reported bidirectional substitution of ethanol and pregnanolone in some rats (Bowen et al , 1999; Gerak et al , 2008), and a sigma receptor agonist fully substituted for pregnanolone (Engel et al , 2001), and for ethanol (Hundt et al , 1998). Variation in endogenous hormones could therefore affect the contribution of these receptor subtypes not included in the current study, particularly sigma receptors.…”
Section: Discussionmentioning
confidence: 99%